Assessment of Tomato Genotypes Using Morpho-physical and Biochemical Traits in Southern Bangladesh - Najmul Hossain; Mehede Hassan Rubel; Md Rafiqul Islam; Pijush Kanti Jhan; Md Mostofa Kamal; Kazi Ishrat Anjum; Md Mohammaed Nuruzzaman; Papia Rahman Moury (Research in Agriculture Livestock and Fisheries, 2025)
Tomato displays significant morpho-physical, and biochemical diversity worldwide, offering valuable resources for strategic use in breeding programs to develop improved lines. The study aimed to identify the suitable varieties based on morpho-physical and biochemical traits. Based on morphological, biochemical, and yield-attributing traits, the cluster was divided into four distinct clusters. Principal component analysis (PCA) determined PC1 accounted for 35.25% of the total variation among genotypes while PC2 explained 15.74% of the total variation observed. The highest plant height (240.7 cm), V15 required minimum time (29.67 DAT) for first flowering, TSS maximum value (5.63) was recorded V5, the highest amount of vitamin C was recorded at (11.72 mg/100 g) in V8, the maximum amount of β-carotene was also recorded (0.37 mg/100 mL) in V1. The highest amount of lycopene (8.91 mg/100 mL) was recorded in V11, the maximum fruit diameter (10.23 cm) was observed in variety V8, the highest fruit length (10.13 cm) was observed in variety V8, the maximum fruit width (10.03 cm) was revealed in variety V8. The maximum number of fruits/plants (34.75) was recorded in V12, the highest single fruit weight (294.3 g) was found in variety V8, the maximum amount of fruits/plant (4615 g) was recorded in variety V7, the largest number of fruits (153.8 t/ha) was also revealed in variety V7. Finally, V7, V8, and V9 are promising varieties in terms of yield-attributing features and biochemical traits. Therefore, V7, V8, V9, and V16 varieties could be utilized in the future breeding program and molecular approaches. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 105-119